Kompetensi Tambahan Dokter Gigi Dalam Peraturan Perundang-Undangan di Indonesia - DASUKI (Faculty of Law- Hang Tuah University, 2021)
The enactment of the Law on Medical Practice has changed the paradigm of health service delivery, dental practice from administration-based regulation to competency which is the domain of the Indonesian Medical Council (KKI) and Professional Organization, the obligation to follow developments in dental science and technology in Continuing Program Development as a lifelong learning process, for competency recertification and additional competency and competency Registration Certificate (STR) as a form of recognition and authority given after participating in CPD in accordance with applicable legal principles and norms so as not to cause problems in its implementation and can open as wide as possible additional competency programs in order to improve professional competence, as a solution to the limitations of specialized services in Indonesia. This study aims to examine the nature of the additional competencies of dentists and institutions with the authority to provide them in the prevailing laws and regulations in Indonesia. It is a normative juridical study with a statute approach, conceptual approach and comparative approach. The essence of Dentist Additional Competence is competence obtained through CPD as a lifelong learning organized by Professional Organizations and institutions authorized to legalize Additional Dentist Competencies in Indonesia, is the Indonesian Medical Council by issuing Additional Competency Registration Certificates in accordance with Law Number 29 Year 2004 Concerning Medical Practices, Indonesian Medical Council Regulations concerning Additional Authorities of Doctors and Dentists, Indonesian Medical Council Regulations concerning the Registration of Doctors and Dentists, Indonesian Medical Council Regulations concerning Additional Qualifications of Specialists and Dentists.